Creating school partnerships that work : a guide for practice and research - Kochan, Frances K.; Griggs, Dana M. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"This is a unique book. If you care about schools and schooling the the way in which partnerships may help to strenghten and improve them and the institutions that partner with them, you shour read it! School partnerships have a long history in the United States. The inception of public schooling was a type of partnership with the community. The concept of local school boards and local control was integral to the establishment of schools and the idea that public education was a public good has deep roots in the country. Partnerships denote relationships which are mutually beneficial to the parties involved and which result in joint benefits for those who create and engage in them. The partnerships presented in this book provide ample evidence of the value and benefits of these arrangements. The book contains stories and research about school partnerships from a variety of groups and perspectives, which are focused upon multiple issues within educational institutions and communities within the United States. The final chapter, presents an analysis across all the partnerships to identify the elements that fostered and hindered their success and the primary lessons learned. This analysis should provide meaningful information for those engaged in developing and operating similar partnerships or those involved in conducting research on or about them. Although the cases presented in this book occur within the United States, the findings may also have relevance for similar initiatives in other countries"-- Provided by publisher.
Keywords: Community and school -- United States.; Community and college -- United States.; Education, Cooperative -- United States.; College-school cooperation -- United States.; Public-private sector cooperation.; Education -- Organizations & Institutions.; Educational administration and organization.; elektronické knihy; electronic books